2016
DOI: 10.1155/2016/1841690
|View full text |Cite
|
Sign up to set email alerts
|

Immune Cells and Inflammation in Diabetic Nephropathy

Abstract: Diabetic nephropathy (DN) is a serious complication of diabetes. At its core, DN is a metabolic disorder which can also manifest itself in terms of local inflammation in the kidneys. Such inflammation can then drive the classical markers of fibrosis and structural remodeling. As a result, resolution of immune-mediated inflammation is critical towards achieving a cure for DN. Many immune cells play a part in DN, including key members of both the innate and adaptive immune systems. While these cells were classic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
90
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(95 citation statements)
references
References 108 publications
4
90
0
1
Order By: Relevance
“…The underlying mechanism is complicated and multiple molecular signalling pathways are involved. The previous studies have revealed the involvement of immune system in the pathophysiology of diabetes, DKD and some other chronic diseases, the proinflammatory events have been found to be triggered by innate and adaptive immunity pathways . Elevated oxidative LDL in serum of patients with diabetes is immunogenic and has been found to be able to induce the production of autoantibody and then form the oxidative LDL immune complex.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The underlying mechanism is complicated and multiple molecular signalling pathways are involved. The previous studies have revealed the involvement of immune system in the pathophysiology of diabetes, DKD and some other chronic diseases, the proinflammatory events have been found to be triggered by innate and adaptive immunity pathways . Elevated oxidative LDL in serum of patients with diabetes is immunogenic and has been found to be able to induce the production of autoantibody and then form the oxidative LDL immune complex.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies have revealed the involvement of immune system in the pathophysiology of diabetes, DKD and some other chronic diseases, the proinflammatory events have been found to be triggered by innate and adaptive immunity pathways. 7,8,25 Elevated oxidative LDL in serum of patients with diabetes is immunogenic and has been found to be able to induce the production of autoantibody and then form the oxidative LDL immune complex. Hypercholesterolaemia is a proinflammatory trigger through the formation of ox-LDL-IC, which enhances the activation of human immunity in DKD and other diabetic complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Macrophages are found in normal kidney and in increased numbers in diseased kidney, well recognized for their pathogenic role in kidney inflammation and fibrosis [14, 15]. Such an increase in the macrophage population has been correlated with the presence of interstitial fibrosis.…”
Section: Introductionmentioning
confidence: 99%